Evaluation of metal removal efficiency and its influence in the physicochemical parameters at two sewage treatment plants - Pipi, Angelo R. F.; Magdalena, Aroldo G. [UNESP]; Giafferis, Giselda P.; da Silva, Gustavo H. R. [UNESP]; Piacenti-Silva, Marina [UNESP] (Springer Nature, 2018)
In sewage treatment plants, physicochemical parameters are highly controlled since treated sewage can be returned to water bodies or reused. In addition, pollutants such as heavy metals also deserve attention due to their potential toxicity. In general, these characteristics of sewage and treated water are evaluated independently, with the support of Brazilian legislation that does not require a routine for the analysis of metals as frequent as for the physicochemical parameters. In this work, 66 samples of raw sewage, treated sewage, and effluents from two treatment plants in the city of Bauru, São Paulo, Brazil, were evaluated to assess the efficiency of the treatment plants in the removal of metals. In addition, the influence of these pollutants on the quantification of physicochemical parameters was evaluated. The quantification of metals was performed using inductively coupled plasma optical spectroscopy (ICP-OES), and Spearman’s test was applied to evaluate correlation between physicochemical parameters and metal content. The main metals found in the samples were Ba, Mn, Zn, Cu, Se, Fe, and Al. The results indicate that concentrations of metals in the aquatic environment can significantly affect the physicochemical parameters, since high concentrations of metals can interfere mainly in the pH, chemical oxygen demand, and dissolved oxygen.
Keywords: Heavy metal; Physicochemical parameters; Sewage treatment plant